Faktor Risiko Kejadian Obesitas pada Remaja SMA Negeri 2 dan SMA Negeri 3 di Kota Pekalongan Tahun 2010 - Susi Muktiharti; Purwanto .; Imam Purnomo.; Rosmiati Saleh (Pena Medika Jurnal Kesehatan, 2011)
Background : Amount of natural Indonesia resident of  increasing in 2001 equal to 22-24% or 48-53 million. Fatness cause some disease and health trouble like heart, hypertension, joint, diabetes mellitus, trouble hormonal. This research aim to know the factor of risk of occurence obesitas in adolescent of High School in region of North Batang. The purpose sampling is counted in 30 people of case group and 30 group people to control . Methode : Data collecting use the kuesioner and balance. Result : Result of research known nothing relation signifikan of among between knowledge storey level about obesitas ( value 1,000) and psychological factor ( value 0,579) with the occurence obesitas at adolescent. There relation signifikan mount the earnings ( value 0,016), pattern eat ( value 0,010), physical activity ( value 0,000), factor genetik ( value 0,002) and sport habit ( value 0,000) with the occurence obesitas at adolescent. better apply the pattern eat healthy, doing activity of physical and sport habit regularly, adolescent specially having history of genetis Key Word : Risk Factor, obesity